Hubungan Antara Komunikasi Situation, Background, Assesment, Recomendation (SBAR) Dengan Pelaksanaan Timbang Terima Pasien di Ruang Rawat Inap Rumah Sakit Dedy Jaya, Brebes, Jawa Tengah - Prayudha Adhi Laksono; Rifai Setiyo Gusti; Adjie Kurniawan; Vip Paramarta (Jurnal Medika Nusantara, 2024)
Currently, in the Inpatient Room at Dedy Jaya Hospital, Brebes, Central Java, as one of the hospitals that follows developments in consumer needs and desires, SBAR communication is also used. Every nurse in the Inpatient Room always carries out SBAR communication with the patients being treated in that room. Nurses communicate SBAR to patients so that there are no errors when weighing patients. The implementation of SBAR communication is carried out by nurses at Dedy Jaya Hospital, Brebes, Central Java because nurses understand the importance of implementing SBAR communication, especially when weighing patients. The initial survey also showed that there were still patient weigh-in sheets that were not filled in completely, resulting in delays in treating some patients. This study aims to analyze the relationship between SBAR communication and the implementation of patient acceptance in the Inpatient Room of the General Services Agency, Dedy Jaya Brebes General Hospital, Central Java. The type of research used is correlational research with a cross sectional design. The population in this study were all nurses in the Inpatient Room at Dedy Jaya Hospital, Brebes, Central Java at the time the research took place, namely 95 people. The sampling technique used in this research was total sampling. The results of the research showed that 55 respondents (69.9 6/) SBAR communication was in the effective category, 67 respondents (61.3 %) included the effective patient acceptance assessment category, and the statistical test results obtained a value of value = 0.000 > ? 0 .05, this shows that there is a relationship between SBAR communication and the implementation of patient acceptance. Researchers suggest that the implementation of SBAR communication can be carried out continuously by nurses in accordance with standard operating procedures so that the implementation of patient acceptance considerations also continues to be better.